ANALYSIS OF COMMUNITY PARTICIPATION IN THE FOREST AND LAND REHABILITATION PROGRAM IN TOTOPO VILLAGE, BILATO SUBDISTRICT, GORONTALO REGENCY - Irwan Bempah; Radi Afriandi E; Sukirman Rahim (Jurnal Hutan Tropis, 2026)
The primary objectives of this study were twofold: to evaluate the extent of community engagement in Forest and Land Rehabilitation (FLR) initiatives and to identify the factors driving this public involvement. Adopting a quantitative research design, primary data were gathered via questionnaire distribution and subsequently analyzed using descriptive statistics alongside multiple linear regression. The empirical results demonstrated that overall community participation in the FLR program stood at 57.66%, falling into the "fairly good" classification. Looking closely at individual dimensions, planning and supervision registered lower scores of 50.00% and 51.94% respectively, placing both in the poor category. Conversely, implementation scored 54.17% (good), while the evaluation stage achieved the highest mark at 74.54% (fairly good). Furthermore, the simultaneous analysis confirmed that age, formal education, household size, financial income, and managed land area collectively exerted a significant influence on FLR participation, accounting for a coefficient of determination of 20.80%. The remaining variance of 79.20% (epsilon) was shaped by unexamined elements, including community competence, individual commitment, local leadership encouragement, financial incentives, and other external variables.